2018
DOI: 10.1101/480293
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Action perception recruits the cerebellum and is impaired in spinocerebellar ataxia patients

Abstract: Our cerebellum has been proposed to generate prediction signals that may help us plan and execute our motor programs. However, to what extent our cerebellum is also actively involved in perceiving the action of others remains to be elucidated. Using fMRI, we show here that observing goal-directed hand actions of others bilaterally recruits cerebellar Lobules VI, VIIb and VIIIa. Moreover, whereas healthy subjects (n=31) were found to be able to discriminate subtle differences in the kinematics of observed limb … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 71 publications
1
15
0
Order By: Relevance
“…A few studies reported the activation of cerebellum during action observation, but mostly as an additional finding not addressed as a main focus of the work 30 , 34 36 , 49 , 91 . However, a very recent work 42 in which healthy subjects were required to observe reaching-grasping actions clearly shows activation of cerebellar lobules VI, VIIb and VIIIa in both hemispheres. In order to investigate the existence of a mirror matching mechanism 6 in the cerebellum, it is necessary to demonstrate the presence of shared activation between action observation and execution.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…A few studies reported the activation of cerebellum during action observation, but mostly as an additional finding not addressed as a main focus of the work 30 , 34 36 , 49 , 91 . However, a very recent work 42 in which healthy subjects were required to observe reaching-grasping actions clearly shows activation of cerebellar lobules VI, VIIb and VIIIa in both hemispheres. In order to investigate the existence of a mirror matching mechanism 6 in the cerebellum, it is necessary to demonstrate the presence of shared activation between action observation and execution.…”
Section: Discussionmentioning
confidence: 95%
“…Only recently, in humans, it has been proposed that aside from the cortical MNS, other subcortical areas, among which the cerebellum and the basal ganglia, might be involved in action observation 30,[34][35][36][37][38][39][40][41] . In particular, a very recent study 42 directly addressed the issue of the localization of cerebellar sectors recruited during grasping action observation, showing activation of specific lobules (VI, VIIb and VIIIa) and suggesting, on the basis of the used task, that human cerebellum is actively involved in perceiving the kinematics of the hand actions of other individuals. Another recent study 43 comparing observation and execution of a grip force task, showed shared activation in both anterior and posterior cerebellum, with linear and non-linear correlations, respectively, between BOLD signal and the level of applied or detected force.…”
mentioning
confidence: 99%
“…Furthermore, higher t-values were observed when the group sizes were bigger and the subjects viewed the stimuli only once . While these are indirect observations from the data presented here, it can be clearly seen from It should be noted that all the sequences used in the current acquisition were able to identify the core regions that have been shown to be a part of the action observation network (Abdelgabar et al, 2018;. ROC analyses suggest a strong concordance between the outcomes of different sequences (tables 3, 5).…”
Section: Discussionmentioning
confidence: 55%
“…2.4 Reference study As a reference for some of the analyses performed to test the effect of accelerated acquisition, we used a previously acquired dataset. Data from this previous study (Abdelgabar et al, 2018) consisted of fMRI data from an independent group of 31 subjects. Images included an anatomical scan and a functional run where the subjects viewed the same action observation paradigm used in this study (CA and CC blocks of 7s).…”
Section: Image Acquisitionmentioning
confidence: 99%
See 1 more Smart Citation